2015
DOI: 10.1007/s11547-015-0578-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between MRI and CEUS in the follow-up of patients with blunt abdominal trauma managed conservatively

Abstract: MRI allowed to make a better assessment of injuries than CEUS, allowing also a temporal stage of lesions. Infact, there are different evolution stages corresponding to accurate imaging findings. To our knowledge, this is the first study that describes the evolution of blood collection in parenchymal abdominal organs. Therefore, in patients who underwent abdominal traumatic injuries conservatively treated, the follow-up at 1 month can be made by MRI, due to its panoramicity and its high contrast resolution, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 16 publications
0
30
0
Order By: Relevance
“…Four citations were excluded because two studies included only patients with CT-confirmed solid organ injury 22, 23 , one was duplicated report 16 , and one is a case series report 24 . As a result, a total of 10 studies were included in the study and 9 were included for meta-analysis 14, 15, 25–32 .
Figure 1PRISMA flow chart of study inclusion. The initial search identified 421 citations.
…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Four citations were excluded because two studies included only patients with CT-confirmed solid organ injury 22, 23 , one was duplicated report 16 , and one is a case series report 24 . As a result, a total of 10 studies were included in the study and 9 were included for meta-analysis 14, 15, 25–32 .
Figure 1PRISMA flow chart of study inclusion. The initial search identified 421 citations.
…”
Section: Resultsmentioning
confidence: 99%
“…Most studies investigated the three major solid organs including kidney, spleen and liver. One study investigated diagnostic accuracy of CEUS on adrenals and found that CEUS missed two adrenal lesions as compared with CT 14 . Valentino’s study included patients with blunt abdominal trauma in which they among other injuries identified lesions in the pancreas and adrenals 29 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations